Integration of topic-specific pedagogical content knowledge components in secondary school science teachers’ reflections on biology lessons - Thumah Mapulanga; Yaw Ameyaw; Gilbert Nshogoza; Anthony Bwalya (Discover Education, 2024)
Abstract Teachers’ reflections on their practice are a powerful tool for measuring and supporting their professional knowledge. Pedagogical content knowledge is one of the most influential domains of teacher professional knowledge. This multiple-case study investigated the topic-specific pedagogical content knowledge (TSPCK) components that Zambian secondary school science teachers integrate when reflecting on biology lessons. Three teachers from the same school were observed teaching a biology lesson and attended post-observation interviews. Data were mainly collected through lesson plans, lesson observation field notes and post-observation interviews. The data were analysed using in-depth analysis of explicit TSPCK, enumerative and constant comparative approaches. TSPCK maps were constructed to illustrate each teachers’ integration of TSPCK components. The results revealed four features about the integration of TSPCK components: (a) None of the teachers depended solely on a single TSPCK component as they integrated other components (b) The components curricular saliency, students’ prior knowledge and misconceptions, and conceptual teaching strategies were central in the TSPCK maps of all the teachers, while representations and analogies, and what make the topic easy/difficult to teach/learn were least integrated (c) All teachers had different pairs of reciprocal connections among TSPCK components, and (d) All teachers had different pairs of most integrated components. The implications of these findings for science and teacher education research were presented and discussed. It was concluded that teachers’ reflections revealed the integration between TSPCK components and showed them differently. The study recommends investigating teachers’ reflections over several lessons and tracking any changes in their TSPCK integration.